Microvascular dysfunction in patients with diabetes after cardioplegic arrest and cardiopulmonary bypass. (November 2016) - Feng, Jun; Sellke, Frank
Abstract : Purpose of review: The purpose of the current review is to describe the changes of microvascular function in patients with diabetes after cardioplegic arrest and cardiopulmonary bypass (CPB) and cardiac surgery. Recent findings: Cardiac surgery, especially that involving cardioplegia and CPB, is associated with significant changes in vascular reactivity of coronary/peripheral microcirculation, vascular permeability, gene/protein expression, and programmed cell death, as well as with increased morbidity and mortality after surgical procedures. In particular, these changes are more profound in patients with poorly controlled diabetes. Summary: Because alterations in vasomotor regulation are critical aspects of mortality and morbidity of cardioplegia/CPB, a better understanding of diabetic regulation of microvascular function may lead to improved postoperative outcomes of patients with diabetes after cardioplegia/CPB and cardiac surgery.